2007
DOI: 10.7589/0090-3558-43.1.89
|View full text |Cite
|
Sign up to set email alerts
|

New Variants of European Brown Hare Syndrome Virus Strains in Free-Ranging European Brown Hares (Lepus Europaeus) From Slovakia

Abstract: ABSTRACT:Investigations regarding European brown hare syndrome virus (EBHSV) in European brown hares (Lepus europaeus) in Slovakia were undertaken in order to detect the possible presence of EBHSV and to evaluate its phylogenetic position. Liver and/or serum samples were obtained from 135 European brown hares shot by hunters in eight regional hunting areas. From 36 animals corresponding liver and serum samples were available; from the remaining 49 and 50 animals only liver or serum samples were examined, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Although Frolich et al indicated that there is no clear relationship between strains, time of isolation and geographic origin (Frolich et al 2007), the importance of geographic and temporal distributions of the virus strains in evolution has already been considered (Le Gall-Recule at al. 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Although Frolich et al indicated that there is no clear relationship between strains, time of isolation and geographic origin (Frolich et al 2007), the importance of geographic and temporal distributions of the virus strains in evolution has already been considered (Le Gall-Recule at al. 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The newly identified tools provide a set of Y-specific markers to identify the gender of brown hare samples from which gender determination is otherwise impossible (e.g., road kill and fetuses) and allow to identify and to trace patrilines in population genetics and other studies (Frölich et al 2007), necessary for investigations regarding, e.g., the genetic structure of and gene flow within the L.e. metapopulation (Fickel et al 1999 or gender-mediated disease transmission.…”
Section: Y-chromosomal Microsatellitesmentioning
confidence: 99%
“…Diseases such as pseudotuberculosis, brown hare syndrome, pseudococcis and gastrointestinal parasites have been argued to also play a role in explaining population dynamics (Newey & Thirgood 2004) or fitness of adult hares (Couch et al 2012). For other hare species, it has been shown that parasites and diseases cannot sufficiently explain demographics in mountain hares (Haerer et al 2001;Frölich et al 2007;Townsend et al 2009) and snowshoe hares (Murray et al 1998), but do seem to affect body condition and nutritional status.…”
Section: Introductionmentioning
confidence: 96%
“…Intensification of agricultural practices has resulted in loss of crop and landscape diversity, and as such is thought to be the main cause behind the decline of hares in agricultural landscapes (Edwards et al 2000;Smith et al 2005). Other factors may have contributed to the decline but have probably not influenced the long-term population trends (Haerer et al 2001;Frölich et al 2007), and these include increased predator densities (Lindstrom et al 1994;Schmidt et al 2004), intensive hunting (Avril et al 2012(Avril et al , 2014 and diseases (Flux et al 1990;Mitchell-Jones et al 1999;Newey et al 2007). Moreover, these factors probably do not operate in isolation but strongly interact with each other.…”
Section: Introductionmentioning
confidence: 97%